Análisis de problemas en estadística y probabilidad en libros de texto de segundo año de educación secundaria - Sánchez, Nicolás Andrés (Revista Científica, 2017)
At present society demands that every citizen manage to develop the capacity to interpret and question different phenomena present in tables, graphs and data, capacities that must be developed progressively from the earliest years of education. For this, it is also necessary that the resources point to the development of these skills, such as the textbook of Mathematics. The objective of the present work is to analyze the types of problems proposed in two Secondary Mathematics textbooks in the thematic area of Statistics and Probability. Both texts were those that were tendered and distributed free of charge and respond to two different curricular periods: 1) the one in which the old curriculum bases were in force and the other 2) when the current curricula were implemented. The use of the school textbook book by students and teachers assumes the premise that the various tasks proposed should tend to solve problems. The research was carried out through a qualitative methodology through content analysis. The theoretical categories proposed by Díaz and Poblete (2001) were used. Among the results found most routine problems are identified that serve to mechanize processes; The non-routine problems or real context, appear in very few cases.